Establishing self-access from theory to practice - Gardner, David (Cambridge University Press, 1999)
This book examines establishing, maintaining and developing self-access language learning (SALL). While much of the book presents practical ideas dealing with issues related to SALL, they are supported by references to relevant literature and research. This link between theory and practice makes the debate about SALL accessible and makes the book a useful resource for those establishing and running self-access learning facilities, from pre-service teacher trainees to experienced teachers and from managers of self-access centers to administrators